PELAKSANAAN FUNGSI HAK ANGKET DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA (STUDI KASUS HAK ANGKET TENTANG KOMISI PEMBERANTASAN KORUPSI) - Novilistiana, Armila; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
The 1945 Constitution of the Republic of Indonesia of Article 20A Concerning the Functions and Rights of the House of Representative is specifically regulated in Law Number 17 of 2014 juncto Law Number 42 of 2014 juncto Law Number 2 of 2018 concerning the People’s Consultative Assembly, the House of Representatives, the Regional Representative Council, and the Regional House of Representatives (MD3). The relevance of this case is included in Law Number 30 of 2002 concerning the Corruption Eradication Commission. The implementation of the functions and rights of the House of Representatives, in this case, the supervisory function and the inquiry rights, as a constitutional right is manifestation of the implementation of the principle of checks and balances drawn from the concept of Trias Politica for controlling every government action, in which the KPK as independent institution does not allow the interference of other powers. The House of Representative interference in overseeing the implementation of Corruption Eradication The involvement of the DPR through its questionnaire rights to the KPK is considered as an act of political intervention that decreases public trust, so needed in order to find a solution.